Manajemen Fisiologis Tanaman Sayuran dalamSistem Hidroponik di Graha Hidroponik Center, Serang - Vega Yoesepa Pamela; Zulfatun Najah; Muhammad Zein Fauzan; Diva Ayu Anisa; Helvi Delianti (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
Limited agricultural land has encouraged the development of hydroponic systems as an efficient urban farming solution. This study aims to analyse the physiological management and post-harvest handling of vegetable crops at Graha Hydroponic Centre, Serang. The methods used include observation, interviews, and documentation. Results show that understanding plant physiology is crucial in nutrient management, variety selection, and adaptation to environmental and market conditions. A closed circulation irrigation system is used efficiently, and plant health monitoring is done visually. In the post-harvest aspect, the use of edible coatings made from natural ingredients such as cassava starch and ginger extract is proven to be able to extend product freshness without refrigeration. Distribution of crops is done by considering delivery time and the needs of modern markets. Strategies such as weekly crop rotation and provision of backup seedlings are also applied to maintain production continuity. This study demonstrates the integration of simple technology, field experience and post-harvest innovation as a model of sustainable hydroponic farming.